Long-Term Effects of Maternal Medication on Global Quality of Life Measured with SEQOL. Results from the Copenhagen Perinatal Birth Cohort 195961 - Soren Ventegodt; Joav Merrick (The Scientific World Journal)
The Copenhagen Perinatal Birth Cohort 195961 is a prospective longitudinal perinatal study that included all deliveries (over 20 weeks gestation, birthweight over 250 g) that took place at the University Hospital (Rigshospitalet) in Copenhagen, Denmark during the period of September 21, 1959 to December 21, 1961 and used in this follow-up study to investigate the connection between maternal medication during pregnancy and the quality of life of the child 31 to 33 years later. The latest follow-up study from the cohort was performed in 1993 and 7,222 of the surviving children were identified (now aged between 31 and 33 years) and contacted with a nonanonymous questionnaire on several aspects of quality of life issues.There were 4,626 usable responses (f = 2,489, m = 2,131) corresponding to a response rate of 64.1%. Of the 12 groups of medication taking during pregnancy we found, before controlling (using multiple linear regression), that analgesics, chemotherapy, and psychopharmacologica showed links with the quality of life in the child 31 to 33 years later. Barbiturate use (95% was phenemal) showed significant connection to quality of life. After controlling for social and pregnancy factors there was no correlation between quality of life and medication taken by the mother during pregnancy. From this study it is concluded the fetal exposure to the drugs examined showed no measurable long-term effects on quality of life.